Bioresponsive microspheres for on‐demand delivery of anti‐inflammatory cytokines for articular cartilage repair. Issue 3 (12th December 2019) - Park, Eunjae; Hart, Melanie L.; Rolauffs, Bernd; Stegemann, Jan P.; T. Annamalai, Ramkumar
Abstract: Despite innovations in surgical interventions, treatment of cartilage injury in osteoarthritic joints remains a challenge due to concomitant inflammation. Obstructing a single dominant inflammatory cytokine has shown remarkable clinical benefits in rheumatoid arthritis, and similar strategies are being suggested to target inflammatory pathways in osteoarthritis (OA). Here, we describe the utility of gelatin microspheres that are responsive to proteolytic enzymes typically expressed in arthritic flares, resulting in on‐demand and spatiotemporally controlled release of anti‐inflammatory cytokines for cartilage preservation and repair. These microspheres were designed with a net negative charge to sequester cationic anti‐inflammatory cytokines, and the magnitude of the negative charge potential increased with an increase in crosslinking density. Collagenase‐mediated degradation of the microspheres was dependent on the concentration of the enzyme. Release of anti‐inflammatory cytokines from the loaded microspheres directly correlated with the degradation of the gelatin matrix. Exposure of the IL‐4 and IL‐13 loaded microspheres reduced the inflammation of chondrocytes up to 80%. Hence, the delivery of these microspheres in an OA joint can attenuate the stimulation of chondrocytes and the resulting secretion of catabolic factors such as proteinases and nitric oxide. The microsphere format also allows for minimally invasive delivery and is less susceptible to mechanically induced drug release. Consequently, bioresponsive microspheres can be an effective tool for cartilage preservation and arthritis treatment.